2016
DOI: 10.1155/2016/4621039
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Immediate and Sustained Release Cephalexin Administered by Different Routes to Llamas (Lama glama)

Abstract: We investigate the pharmacokinetics of two different cephalexin formulations administered to llamas by the intravenous (IV), intramuscular (IM), and subcutaneous (SC) routes, the minimum inhibitory concentration (MIC) of cephalexin against some Escherichia coli and staphylococci isolated from llamas, and we apply the PK/PD modelling approach, so that effective dosage recommendations for this species could be made. Six llamas received immediate (10 mg/kg, IV, IM, and SC) and sustained (8 mg/kg IM, SC) release c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The determination of MIC was performed in order to evaluate potential antimicrobial resistances. Since no CLSI official breakpoints are available for llamas, and in order to provide a laboratory result, the MIC results (Table 1 ) were evaluated using the bovine clinical breakpoints, even though several authors have observed that llamas, but also other SACs, and bovines present different pharmacokinetics and pharmacodynamics [ 35 , 36 ]. The evaluation, with bovine breakpoints, highlights sensitivity to all antimicrobials tested.…”
Section: Discussionmentioning
confidence: 99%
“…The determination of MIC was performed in order to evaluate potential antimicrobial resistances. Since no CLSI official breakpoints are available for llamas, and in order to provide a laboratory result, the MIC results (Table 1 ) were evaluated using the bovine clinical breakpoints, even though several authors have observed that llamas, but also other SACs, and bovines present different pharmacokinetics and pharmacodynamics [ 35 , 36 ]. The evaluation, with bovine breakpoints, highlights sensitivity to all antimicrobials tested.…”
Section: Discussionmentioning
confidence: 99%
“…), respectively. The MIC90 values of cephalexin against coagulase-positive staphylococci and E. coli were 1.0 μg/ml and 8.0 μg/ml, respectively [59]. But MIC90 value (0.01-0.1 μg/ml) of ceftazidime against E. coli, Salmonella species, Pasteurella haemolytica and P. multocida [45] shows that ceftazidime is more active and efficacious than cephalexin, which can be administered 8 mg/kg i.m.…”
Section: Pharmacokinetics Of Antimicrobials In Wild Goatsmentioning
confidence: 99%
“…But MIC90 value (0.01-0.1 μg/ml) of ceftazidime against E. coli, Salmonella species, Pasteurella haemolytica and P. multocida [45] shows that ceftazidime is more active and efficacious than cephalexin, which can be administered 8 mg/kg i.m. or subcut every 12 or 24 h, respectively [59]. Other modes of administration such as ballistic implants and impregnated beads can be employed for some antimicrobials to avoid frequent administration as seen in cefovecin with very long half-life in dogs and cats, allowing a dosing interval of 14 days [60,61].…”
Section: Pharmacokinetics Of Antimicrobials In Wild Goatsmentioning
confidence: 99%
“…It is effective in the treatment of Staphylococci and Streptococci infections [2]. It was also found to be effective against Escherichia coli [3]. It is listed as a key access antibiotic in the World Health Organization's essential drug list and it is used as a second choice drug in the form of oral delivery for the effective treatment of chronic obstructive pulmonary disease (COPD), pharyngitis, skin, and soft tissue infections [4].…”
Section: Introductionmentioning
confidence: 99%
“…To improve solubility, bioavailability, and therapeutic efficacy, several CEP formulations have been developed. The formulations like immediate and sustained release formulations [3], controlled release matrix tablets [8], silica micro-particles [19], non-ionic microemulsions [5], extended-release matrix tablets [7,20], and gastro-floating tablets [6,21] have been developed and tested. The objective of the current research was to develop a CEP SNEDDS and evaluate it by a titration method.…”
Section: Introductionmentioning
confidence: 99%